The Disassembly Map: A new method to enhance design for product repairability. (20th October 2021) - De Fazio, Francesco; Bakker, Conny; Flipsen, Bas; Balkenende, Ruud
Abstract: Designers and engineers need better tools and methods to create highly repairable products. Design for disassembly and reassembly is an important product related design feature that can enhance repair. In a highly repairable product, the components that fail most often should be easily accessible for repair or replacement. This paper describes the development of a method to visually map the disassembly of a product, showing different routes towards target components. These components can be those with a high potential failure rate (important for repair), embodied environmental impact (important for recycling) and economic value (relevant for component harvesting), depending on the circular strategy under consideration. The 'Disassembly Map' method is set up to guide product design and is aligned with the most recent research and standards on product repairability. The ease of disassembly is assessed on Four main design parameters are considered in this method to assess the ease of disassembly of: disassembly sequence/depth, type of tools, fastener reusability/reversibility, and disassembly time. In contrast to most of the related literature found, the Disassembly Map method is not based on the use of an algorithm for the automatic calculation of optimised disassembly sequences. It asks designers and engineers to analyse each disassembly step using standardized visual elements based on the ease of Disassembly Metric (eDiM) and the Maynard Operation Sequence Technique (MOST). Insights gathered from this analysis and the resulting visualisation can be used in an iterative product development process. The method was developed by analysing seven vacuum cleaners. Its effectiveness was then tested by redesigning one of them, enhancing its repairability. Highlights: Mapping product architecture is essential to identify design features hindering repairability. The Disassembly Map is a simple and intuitive method for Design for Repair, based on product architecture mapping. To create better repairable products, designers should consider design for disassembly in early design stages. A key product related design feature to improve repairability is optimising target component accessibility. Different types of disassembly interdependences between components can impact design for disassembly.